A Literature Review on the Integration of Plant Anatomical Principles in the Optimization of Vertical-Axis Wind Turbine Blade Design - Habiburahman, Novan Habiburrahman; Priyanti, Novy Ary; Hariadi, Agung; Muttaqin, M. Zainul (Universitas Kristen Cipta Wacana, 2025)
The development of renewable energy technologies increasingly demands innovative, efficient, and environmentally friendly designs. Vertical Axis Wind Turbines (VAWT) are among the promising energy conversion systems suitable for urban and marine applications. However, aerodynamic efficiency and environmental adaptability remain key challenges. In contrast, the anatomical structures of plants particularly leaves and stems have naturally evolved to optimize interactions with airflow and sunlight, making them a rich source of inspiration for technological innovation. This article presents an interdisciplinary literature review exploring how principles of plant anatomy can be integrated into VAWT blade design to enhance aerodynamic performance and energy conversion efficiency. Through a comprehensive analysis of literature from mechanical engineering and plant biology, this study identifies key anatomical features such as surface curvature, venation patterns, and epidermal textures as having direct relevance to drag reduction, turbulent flow regulation, and lift enhancement. This review aims to open new directions for bioinspired design approaches in wind turbine development and strengthen the collaboration between engineering and biological sciences in advancing sustainable energy technologies.